Music and musicians in Renaissance cities and towns (Cambridge University Press, 2001)
This interdisciplinary collection examines musical culture in the towns and cities of Renaissance Europe and the New World. Although musicologists have already investigated such topics, lack of familiarity with (urban) historical methodologies has often resulted in failure to explore fully the ways in which the urban environment had an impact on musical activity of all kinds. This book aims to integrate musicological and urban-historical approaches in order to obtain a fuller understanding of the processes and circumstances that had an impact on Renaissance music and musicians